Tightly focused linearly and radially polarized beam effect on the LSPR peak with varying particle size - Sarita; Jha R.; Singh R.K. (My University, 2025)
Interactions of gold and silver spherical nanoparticles (NPs) of a wide range of radius size with tightly focused beams are investigated for a wide range of wavelengths. The scattering of tightly focused beams with a single NP of varying size is examined using a generalized Mie theory and average intensity enhancement in the near-field due to localized surface plasmons is examined for different tightly focused beams. A multipole expansion approach is used to observe the contribution of modes in shaping the scattered light intensity. Influence of particle size and tightly focused beam on intensity enhancement factor is investigated and a shift in localized surface plasmon resonance (LSPR) peak towards higher wavelength is observed with increasing particle size. Maximum intensity enhancement factor due to scattering of different incident beams by a metallic NP is theoretically examined and reported. Gold and silver NP having radius size ranging from 30-60 nm and 1-15 nm respectively showed a maximum intensity enhancement factor in different media. A significant enhancement for the tightly focused radially polarized beam is observed for gold and silver NPs of radius size between 50 nm and 100 nm. Variation towards higher wavelength in LSPR peak due to involvement of higher order of multipoles, and the surrounding medium are also examined in detail. © 2023 IOP Publishing Ltd.